2018
DOI: 10.1002/hpja.185
|View full text |Cite
|
Sign up to set email alerts
|

Why do the public support or oppose obesity prevention regulations? Results from a South Australian population survey

Abstract: Sociodemographic differences in support appeared to reflect gendered responsibilities for food provision and concerns about the material constraints of socioeconomic deprivation. Engagement with target populations may offer insights to optimise the acceptability of regulations and minimise unintended social consequences. SO WHAT?: Resistance to regulations amongst socioeconomically disadvantaged target populations warrants attention from public health advocates. Failure to accommodate concerns identified may f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
43
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(54 citation statements)
references
References 41 publications
10
43
1
Order By: Relevance
“…Despite their being evidence of public support for menu labelling [64,65,95], further efforts are required to engage consumers in order to increase uptake and demand (e.g. through consumer education mass media campaigns) [96,97].…”
Section: Implications and Recommendations For Practice Policy And Rmentioning
confidence: 99%
“…Despite their being evidence of public support for menu labelling [64,65,95], further efforts are required to engage consumers in order to increase uptake and demand (e.g. through consumer education mass media campaigns) [96,97].…”
Section: Implications and Recommendations For Practice Policy And Rmentioning
confidence: 99%
“…7 Understanding public opinion is also important for public health advocates, as this information can be utilized to demonstrate support for different policy issues. 10 Generally, advocacy success increases with the proportion of the public supporting the policy position. 6 Detailed information on public opinion can also provide practical guidance to advocates by informing the appropriate framing of messages for different audience segments to increase levels of support for a policy issue.…”
Section: Introductionmentioning
confidence: 99%
“…The acceptance of SSB taxation was also reported by Farrell et al in 2019. According to this team, 42% of the Australian population were in favour of the tax imposed on SSB and that the greatest opposition to the tax was expressed by the most disadvantaged group [58]. The analysis performed by Miller et al on the data coming from two surveys: a face-to-face survey conducted in 2014 and CATI survey in 2017, also showed that persons who attained higher levels of education expressed greater support for SSB tax than those with lower levels of education [59].…”
Section: Discussionmentioning
confidence: 99%